Acceleration of electrons at wakefield excitation by a sequence of relativistic electron bunches in dielectric resonator - Kiselev, V.A.; Linnik, A.F.; Mirnyj, V.I.; Onishchenko, I.N.; Uskov, V.V. (Вопросы атомной науки и техники, 2009)
Method is proposed to divide a regular sequence of electron bunches into parts of bunches driving wakefield and
witness bunches, which should be accelerated. It allows to avoid the necessity of additional electron accelerator for
witness bunches producing and the necessity of precision short time techniques of injection phase adjusting. The idea
concludes to the frequency detuning between bunches repetition frequency and the frequency of the fundamental mode
of excited wakefield. Experiments were carried out on the linear resonant accelerator "Almaz-2", which injected in the
dielectric resonator a sequence of 6000 short bunches of relativistic electrons with energy 4.5МeV, charge 0.16 nC and
duration 60psec each, the repetition interval 360 ps. Frequency detuning was entered by change of frequency of the
master generator of the klystron within the limits of one percent so that the phase taper on the length of bunches
sequence achieved 2π. Energy spectra of electrons of bunches sequence, which have been propagated through the
dielectric resonator are measured and analyzed. Запропоновано метод поділення регулярної послідовності електронних згустків на згустки, що збуджують
кільватерне поле і згустки-свідки, які повинні прискорюватися. Це дозволяє уникнути необхідності в
додатковому прискорювачі для отримання згустків-свідків і прецизійної короткоімпульсної техніки для вибору
фази інжекції. Ідея зводиться до введення розладу між частотою проходження згустків і частотою основної
моди кільватерного поля, що збуджується. Експерименти проводились на лінійному резонансному
прискорювачі «Алмаз-2», який інжектував в діелектричний резонатор послідовність 6000 коротких згустків
релятивістських електронів з енергією 4.5 МеВ, зарядом 0.16 нКл і тривалістю кожного 60 пс, інтервал
повторення 360 пс. Розлад частоти вводився змінюванням частоти задавальног генератора клістрона в межах
одного процента, так що набіг фази на довжині послідовності згустків сягав 2π. Вимірювались і аналізувались
енергетичні спектри електронів послідовності згустків, що пройшли через діелектричний резонатор. Предложен метод разделения регулярной последовательности электронных сгустков на сгустки,
возбуждающие кильватерное поле, и сгустки-свидетели, которые должны ускоряться. Это позволяет избежать
необходимости в дополнительном ускорителе для получения сгустков-свидетелей и прецизионной коротко-
импульсной техники для выбора фазы инжекции. Идея сводится к введению расстройки между частотой
следования сгустков и частотой основной моды возбуждаемого кильватерного поля. Эксперименты
проводились на линейном резонансном ускорителе «Алмаз-2», который инжектировал в диэлектрический
резонатор последовательность 6000 коротких сгустков релятивистских электронов с энергией 4.5МэВ, зарядом
0.16 нКл и длительностью каждого 60 пс, время повторения 360 пс. Расстройка частоты вводилась изменением
частоты задающего генератора клистрона в пределах одного процента, так что набег фазы на длине
последовательности сгустков достигал 2π. Измерялись и анализировались энергетические спектры электронов
последовательности сгустков, прошедших через диэлектрический резонатор.